If functions transfer some a to b via some formula, then inverse of such functions transfer b to a via some other formula.
Hope this helps.
Answer:
true
Step-by-step explanation:
There are some area calculators on google if you need but I will try work it out..... if I don’t know I won’t send another answer
If the -1 is not included, then your answer is 3.17.
2(3x-4)=11
3x2=6 and -4x2= -8
6x-8=11
+8 +8
6x=19
/6 /6
X= 3.17
Answer:
y=-5/4x-8
Step-by-step explanation:
2=-5/4(-8)+b
2=10+b
2-10=10-10b
-8=b